Effect of expression of immunohistochemical marker Ki-67 on the life expectancy of patients with gastric cancer 0-III stages - O. M. Levyk; A. I. Shevchenko; V. A. Tumanskiy; A. V. Evseyev (Patologìâ)
In Ukraine 60,9% of patients with gastric cancer die within 1 year after ascertainment of diagnosis.